2018
DOI: 10.1002/jobm.201800314
|View full text |Cite
|
Sign up to set email alerts
|

Environmental filtering drives bacterial community structure and function in a subalpine area of northern China

Abstract: Microbial community assembly is affected by the trade-off between deterministic and stochastic processes, but the mechanisms underpinning their relative influences remain elusive. This knowledge gap strongly limits our ability to predict the effect of environmental filtering on microbial community structure and function. To improve the understanding of mechanisms underlying community assembly processes, we investigated bacterial community structure and function on a subalpine shady slope and a sunny slope in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Additionally, community assembly offers a framework to explore the mechanisms driving microbial community dynamics. Community assembly theories, such as the niche theory [29] and the neutral theory [30], have provided conceptual frameworks to elucidate the underlying mechanisms driving the composition and structure of soil microbial communities [31,32]. Various studies have suggested that soil bacterial community assembly is combined and driven by deterministic and stochastic processes.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, community assembly offers a framework to explore the mechanisms driving microbial community dynamics. Community assembly theories, such as the niche theory [29] and the neutral theory [30], have provided conceptual frameworks to elucidate the underlying mechanisms driving the composition and structure of soil microbial communities [31,32]. Various studies have suggested that soil bacterial community assembly is combined and driven by deterministic and stochastic processes.…”
Section: Introductionmentioning
confidence: 99%
“…Environmental factors, such as precipitation, wind, and solar radiation, have been shown to play an essential role in determining patterns of phyllosphere microbial community colonization [9]. Microbial communities undergo natural selection in every ecosystem, leading to variations in microbial composition under different circumstances [10,11], suggesting that environmental forces play a significant part in introducing microorganisms to the plant phyllosphere. At the same time, phyllosphere microbial communities have the potential to influence plant biogeography and ecosystem function through their influence on plant performance under different environmental conditions [12][13][14].…”
Section: Introductionmentioning
confidence: 99%